Regulating Lithium Plating/Stripping Behavior by a Composite Polymer Electrolyte Endowed with Designated Ion Channels. Issue 52 (9th November 2022) - Hu, Ajuan; Sun, Zongqiang; Hou, Qing; Duan, Jianing; Li, Chen; Dou, Wenjie; Fan, Jingmin; Zheng, Mingsen; Dong, Quanfeng
Abstract: The urgent demand for high energy and safety storage devices is pushing the development of lithium metal batteries. However, unstable solid electrolyte interface (SEI) formation and uncontrollable lithium dendrite growth are still huge challenges for the practical use of lithium metal batteries. Herein, a composite polymer electrolyte (CPE) endowed with designated ion channels is fabricated by constructing nanoscale Uio66‐NH2 layer, which has uniformly distributed pore structure to regulate reversible Li plating/stripping in lithium metal batteries. The regular channels within the Uio66‐NH2 layer work as an ion sieve to restrict larger TFSI − anions inside its channels and extract Li + across selectively, which result in a high Li‐ion transference number ( t Li + ${t_{{\rm{L}}{{\rm{i}}^{\bm{ + }}}}}$ ) of 0.6. Moreover, CPE provides high ion conductivity (0.245 mS cm −1 at room temperature) and expanded oxidation window (5.1 V) and forms a stable SEI layer. As a result, the assembled lithium metal batteries with CPE exhibit outstanding cyclic stability and capacity retention. The Li/CPE/Li symmetric cell continues plating/stripping over 500 h without short‐circuiting. The Li/CPE/LFP cell delivers a reversible capacity of 149.3 mAh g −1 with a capacity retention of 99% after 100 cycles. Abstract : A composite polymer electrolyte with designated ion channels is prepared to regulate highly reversible Li + plating/stripping behavior in Li metal batteries. The uniform Uio66‐NH2 layer with intrinsic nanochannels can restrict larger TFSI − anions inside its regular channels and homogenize the distribution of Li + on the surface of lithium metal anode to render a smooth dendrite‐free morphology.